Analisis Kinerja Keuangan Perusahaan Daerah Air Minum Kota Baubau dan Kabupaten Buton - Sri Sumantri (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2021)
This study aims to determine and explain the performance of PDAM Baubau City and PDAM Buton Regency based on the Decree of the Minister of Home Affairs No. 47 of 1999, as well as to compare which PDAMs have better performance (PDAM Baubau City or PDAM Kabupaten Buton) for the 2018-2019 period. Financial performance is measured by profitability ratios, liquidity ratios, and solvency ratios. This study uses secondary data from the financial statements of water companies in Baubau City and Buton Regency in 2018-2019. The data analysis technique used is an analysis with a comparative method, which is to compare the results of the financial performance of PDAM Kota Baubau and PDAM Kabupaten Buton based on the Decree of the Minister of Home Affairs No. 47 of 1999. This study shows that the financial performance of PDAM Baubau City and Wakatobi Regency for the last 2 years (2018-2019) which, if associated with the Decree of the Minister of Home Affairs No. 47 of 1999, the financial performance aspects of these two companies are included in the poor category.Penelitian ini bertujuan Untuk mengetahui dan menjelaskan kinerja PDAM Kota Baubau dan PDAM Kabupaten Buton berdasarkan Surat Keputusan Mendagri No. 47 tahun 1999, serta untuk membandingkan PDAM mana yang memliki kinerja yang lebih baik (PDAM Kota Baubau atau PDAM Kabupaten Buton) periode 2018-2019. Kinerja keuangan diukur dengan rasio profitabilitas, rasio likuiditas, dan rasio solvabilitas. Penelitian ini menggunakan data sekunder laporan keuangan perusahaanAir Minum Kota Baubau dan Kabupaten Buton tahun 2018-2019. Teknik analisis data yang digunakan adalah analisis dengan metode perbandingan yaitu membandingkan hasil kinerja keuangan PDAM Kota Baubau dan PDAM Kabupaten Buton berdasarkan Surat Keputusan Menteri Dalam Negeri No. 47 tahun 1999. Penelitian ini menunjukkan Bahwa kinerja keuangan PDAM Kota Baubau dan Kabupaten Wakatobi selama 2 tahun terakhir (2018-2019) yang jika dikaitkan dengan Surat Keputusan Menteri Dalam Negeri No. 47 Tahun 1999, maka aspek kinerja keuangan kedua peusahaan ini termasuk dalam kategori kurang.